Polyphase zircon in ultrahigh-temperature granulites (Rogaland, SW Norway): constraints for Pb diffusion in zircon - Moller, A.; O'Brien, P.; Kennedy, Allen; Kroner, A. (Blackwell Publishing, 2002)
SHRIMP U-Pb ages have been obtained for zircon in granitic gneisses from the aureole of the Rogaland anorthosite-norite intrusive complex, both from the ultrahigh temperature (UHT; >900 C pigeonite-in) zone and from outside the hypersthene-in isograd. Magmatic and metamorphic segments of composite zircon were characterised on the basis of electron backscattered electron and cathodoluminescenceimages plus trace element analysis. A sample from outside the UHT zone has magmatic cores with an age of 1034 + or- 7 Ma (2r, n= 8) and 1052 + or - 5 Ma (1r, n=1) overgrown by M1 metamorphic rims giving ages between 1020 + or- 7 and 1007 + or - 5 Ma. In contrast, samples from the UHT zone exhibitfour major age groups: (1) magmatic cores yielding ages over 1500 Ma (2) magmatic cores giving ages of 1034 + or - 13 Ma (2r, n=4) and 1056 + or - 10 Ma (1r, n=1) (3) metamorphic overgrowths ranging in age between 1017 + or - 6 Ma and 992 + or - 7 Ma (1r) corresponding to the regional M1 Sveconorwegiangranulite facies metamorphism, and (4) overgrowths corresponding to M2 UHTcontact metamorphism giving values of 922 + or - 14 Ma (2r, n=6). Recrystallized areas in zircon from both areas define a furtherage group at 974 + or - 13 Ma (2r, n=4). This study presents the first evidence from Rogaland for newgrowth of zircon resulting from UHT contact metamorphism. More importantly, it shows the survival of magmatic and regional metamorphic zircon relics in rocks that experienced a thermal overprint of c.950 C for at least 1 Myr. Magmatic and different metamorphic zones in the same zircon are sharply bounded and preserve original crystallization age information, a result inconsistent with some experimental data on Pb diffusion in zircon which predict measurable Pb diffusion under suchconditions. The implication is that resetting of zircon ages by diffusion during M2 was negligible in thesedry granulite facies rocks. Imaging and Th/U-Y systematics indicate that the main processes affecting zircon were dissolution-reprecipitation in a closed system and solid-state recrystallization during andsoon after M1.